Impact of Function Focused Care and Physical Activity on Falls in Assisted Living Residents. Issue 1 (March 2020) - Resnick, Barbara; Galik, Elizabeth; Boltz, Marie; Zhu, Shijun; Fix, Steven; Vigne, Erin
Background: There continues to be a belief among nurses, patients, and families that physical activity increases the risk of falling. Purpose: The purpose of this study was to test the hypothesis that controlling for age, function, cognition, medication use, gender, comorbidities, and cognition, residents who are exposed to Function Focused Care for Assisted Living (FFC-AL-EIT) and engage in moderate levels of physical activity would not be more likely to fall. Methods: This was a secondary data analysis using data from the first two cohorts of a randomized trial testing FFC-AL-EIT in the United States. Results: The study included 381 residents, the majority of whom were female (70%), white (97%), with a mean age of 87.72 (standard deviation = 7.47). Those who engaged in more moderate-intensity physical activity were 1% less likely to fall (odds ratio = .99, p  = .03). There was no significant association between exposure to function focused care and falling (odds ratio = 1.58, p  = .09). Conclusion: There was no indication that those who were exposed to function focused care or those who engaged in moderate-level physical activity were more likely to fall. In fact, engaging in moderate-level physical activity was noted to be slightly protective of falling.